A hybrid PSS–SSSC GA-stabilization scheme for damping power system small signal oscillations. (February 2016) - Jolfaei, Mohammad Ghanbari; Sharaf, Adel M.; Shariatmadar, Seyed Mohammad; Poudeh, Mohammad Bayati
Highlights: Complete review of the previous methods and study of their shortcomings. Use of the most update articles and formulas in the area of management and exploitation. Introduce the new effective hybrid controller for SSSC in power system. Simultaneously adjusting the PSS and SSSC parameters. Good and effective damping on power system oscillations. Abstract: Nonlinear and fast quasi dynamic type loads of different time-varying ranges are introduced to the electric grid systems due to renewable Energy, distributed Generation and Power electronic AC–DC–AC interface converters used in several parts of the power network, the dynamic small signal electromechanical modes are destabilized and dynamic stability limits of AC system is reduced. FACTS – Flexible AC Transmission Devices with conventional coordinated power system Stabilizers are utilized to improve dynamic stability margins and damp unstable and oscillatory electromechanical modes of oscillations. Coordinated Flexible Soft Computing Control Strategies are proposed for damping modes of through supplementary damping torques provided by Static Synchronous Series Compensator – SSSC in addition to classical Power System stabilizers – PSS. To coordinate the dual action of both SSSC and PSS devices a Genetic algorithm Tuning Controller is applied. The dynamic simulation results for optimized controllers are validated using Matlab/Simulink Software Environment.